Women with endometriosis improved their peripheral antioxidant markers after the application of a high antioxidant diet - Casanueva Esther; Tolentino Mari C; Jiménez-Zamudio Luis; Burrola-Méndez Soraya; Aburto-Soto Tania; Mier-Cabrera Jennifer; Hernández-Guerrero César (BMC, 2009)
Abstract Background Oxidative stress has been identified in the peritoneal fluid and peripheral blood of women with endometriosis. However, there is little information on the antioxidant intake for this group of women. The objectives of this work were 1) to compare the antioxidant intake among women with and without endometriosis and 2) to design and apply a high antioxidant diet to evaluate its capacity to reduce oxidative stress markers and improve antioxidant markers in the peripheral blood of women with endometriosis. Methods Women with (WEN, n = 83) and without endometriosis (WWE, n = 80) were interviewed using a Food Frequency Questionnaire to compare their antioxidant intake (of vitamins and minerals). Then, the WEN participated in the application of a control (n = 35) and high antioxidant diet (n = 37) for four months. The high antioxidant diet (HAD) guaranteed the intake of 150% of the suggested daily intake of vitamin A (1050 μg retinol equivalents), 660% of the recommended daily intake (RDI) of vitamin C (500 mg) and 133% of the RDI of vitamin E (20 mg). Oxidative stress and antioxidant markers (vitamins and antioxidant enzymatic activity) were determined in plasma every month. Results Comparison of antioxidant intake between WWE and WEN showed a lower intake of vitamins A, C, E, zinc, and copper by WEN (p < 0.05, Mann Whitney Rank test). The selenium intake was not statistically different between groups. During the study, the comparison of the 24-hour recalls between groups showed a higher intake of the three vitamins in the HAD group. An increase in the vitamin concentrations (serum retinol, alpha-tocopherol, leukocyte and plasma ascorbate) and antioxidant enzyme activity (superoxide dismutase and glutathione peroxidase) as well as a decrease in oxidative stress markers (malondialdehyde and lipid hydroperoxides) were observed in the HAD group after two months of intervention. These phenomena were not observed in the control group. Conclusion WEN had a lower intake of antioxidants in comparison to WWE. Peripheral oxidative stress markers diminished, and antioxidant markers were enhanced, in WEN after the application of the HAD.